New records of desmids from Mithamoin haor in Kishoreganj, Bangladesh - Ahmed, Tanvir; Tonne , Nur E Taj Jahan; Alfasane , Md Almujaddade (Bangladesh Journal of Plant Taxonomy, 2024)
A total of 6 species of Desmidiaceae were recorded as new record from Mithamoin haor in Bangladesh. There are namely, Staurastrum mucronatum var. subtriangulare West & West, Staurastrum platycerum Joshua, Staurodesmus tortus (Grobland) Teiling, Cosmarium manomazum P.M. Lundell, Desmidium bailey var. caclatum (Kirchn.) Nordstedt and Spondylosium lundellii var. lundellii Borge. After a careful and intense review on the list of desmids algae of Bangladesh, all these six species are found to be new addition, and they are described here for the first time in Bangladesh so far. Bangladesh J. Plant Taxon. 31(2): 275-278, 2024 (December)